The Effects of RAFT Strategy Towards Students' Writing Skills on Writing Descriptive Text of 7th Grade Students at SMPN 3 Cikarang Barat - Hermariyanti Kusumadewi (Wanastra: Jurnal Bahasa dan Sastra, 2023)
The Effects of RAFT Strategy on Students' Writing Skills on Writing Descriptive Text of 7th Grade Students at SMPN 3 Cikarang Barat. This study aims to find out the effect of using the RAFT Strategy on students' descriptive text writing skills in the second semester of 7th Grade Students at SMPN 3 Cikarang Barat. This research uses descriptive quantitative method. The research method used is descriptive quantitative method. Data collection techniques using interviews, observation, tests and documentation. Aspects that are assessed in writing descriptive texts are the results of learning to write descriptive texts, evaluations, and summaries. The results of the research on students' descriptive text writing skills using the RAFT strategy in grade VII students of SMPN 3 Cikarang Barat obtained an average score of 51.51 with a sufficient category. This means that students as a whole are able to write descriptive text using the RAFT strategy. As evidenced by the number of 184 students, 36 of them scored above the KKM (Minimum Completeness Criteria) and 16 students scored below the KKM. Keywords: RAFT Strategy, Writing Skills, Descriptive Text